2001
DOI: 10.1159/000049318
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Comorbidity in Referred Children and Adolescents with Dysthymic Disorder

Abstract: Anxiety disorders are common in patients with depressive disorders. This preliminary study investigated some clinical correlates of comorbidity between dysthymic disorder (DD) and generalized anxiety disorder (GAD) in a clinically referred sample of children and adolescents. After psychiatric evaluation, including a diagnostic clinical interview (DICA-R), 51 patients (25 males and 26 females, mean age 13.1 years) with an index diagnosis of DD associated with GAD were compared with 22 patients (13 males and 9 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
(42 reference statements)
1
10
0
Order By: Relevance
“…This is consistent with rates reported in three previous studies [21,23,24], but higher than the rates of 17% and 30% in more recent reports [50,51]. rule violation and pathological lying) [51,52] than those with one diagnosis only (pure DD or pure major depressive disorder). rule violation and pathological lying) [51,52] than those with one diagnosis only (pure DD or pure major depressive disorder).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with rates reported in three previous studies [21,23,24], but higher than the rates of 17% and 30% in more recent reports [50,51]. rule violation and pathological lying) [51,52] than those with one diagnosis only (pure DD or pure major depressive disorder). rule violation and pathological lying) [51,52] than those with one diagnosis only (pure DD or pure major depressive disorder).…”
Section: Discussionsupporting
confidence: 92%
“…Chorpita et al's finding supports our finding that the CDI's accuracy to detect an additional diagnosis of GAD in children with SOP was nearly significant. Second, several investigators have found that GAD is in fact highly comorbid with depression in children and adolescents (e.g., Chavira, Stein, Bailey, & Stein, 2004;Curry et al, 2004;Masi et al, 2000;Masi, Mucci, Favilla, & Millepiedi, 2001;Masi, Mucci, Favilla, Romano, & Poli, 1999;Verduin & Kendall, 2003). Thus, the higher symptoms of depression seen in the comorbid SOP-GAD group in comparison to the SOP-only group, despite a lack of depressive disorder diagnoses, may be partly explained by the secondary diagnosis of GAD.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study (O’Neil-Rodriguez & Kendall, 2012), 58% of youth diagnosed with an anxiety disorder reported suicidal ideation. Some studies have uncovered an association between anxiety and suicidality independent of depression (Boden, Fergusson, & Horwood, 2007; Foley, Goldston, Costello, & Angold, 2006; Ghaziuddin, King, Naylor, & Ghaziuddin, 2000; Goldston et al, 2009; Liu et al, 2006; Masi, Mucci, et al, 2001; O’Neil, Puleo, Benjamin, Podell, & Kendall, 2012; O’Neil-Rodriguez & Kendall, 2012) whereas a few others have not (Barbe et al, 2005; Esposito & Clum, 2002; Greene, Chorpita, & Aukahi, 2009; Ryan et al, 1987; Strauss et al, 2000). It may be that emotion dysregulation (Southam-Gerow & Kendall, 2000; Garber, Braafladt, & Weiss, 1995; Keenan, Hipwell, Hinze, & Babinski, 2009; Silk, Steinberg, & Morris, 2003; Suveg, Hoffman, Zeman, & Thomassin, 2009) and distress tolerance (Ellis, Fischer, & Beevers, 2010; Huang, Szabó, & Han, 2009; Keough, Riccardi, Timpano, Mitchell, & Schmidt, 2010; Daughters et al, 2009) constructs related to both depression and anxiety, drive their associations with suicidality (Zlotnick, Donaldson, Spirito, & Pearlstein, 1997; Tamas et al, 2007; Nock & Mendes, 2008; Anestis, Bagge, Tulle, & Joiner, 2011).…”
Section: Descriptive and Developmental Variablesmentioning
confidence: 99%
“…One explanation has to do with severity of the disorder (e.g., in community versus hospitalized youth), type of anxiety disorder, and the operational definition of suicidality (O’Neil-Rodriguez & Kendall, 2012). Although few studies have been adequately powered to examine suicidality in relation to each individual anxiety disorder, studies have supported specific relationships with GAD (Foley et al, 2006; Goldston et al, 2009; Masi, Mucci et al, 2001) and SAD (Liu et al, 2006; Masi, Mucci et al, 2001). The operational definition of suicidality (e.g., ideation; intent; capability of acting on intent) is especially relevant.…”
Section: Descriptive and Developmental Variablesmentioning
confidence: 99%